Heparin Small Pool High Yield Purified Factor VIII: In Vivo Recovery and Half-Life of Routinely Produced Freeze-Dried Concentrate - Sibinga, C T Smit; Daenen, S M G J; Imhoff, G W van; Maas, A; Das, P C (Thrombosis and Haemostasis, 1984)
New approaches and techniques for improving source material collection and Factor VIII production at Blood Bank level have been reported recently.Heparin has been shown to be of importance in increasing yields and stability of FVIII in the purification and concentration process. Work has been done to develop on a routine scale the heparin double cold precipitation technique for the production of a freeze-dried high yield purified FVIII concentrate.The product has been tested clinically in 4 severe hemophilia A patients for recovery, half-life and acute side-effects, using two dosages over 8 infusions. There was no significant difference between the two dosages. Mean recovery 99.1% and mean halflife 8 hr, ranging from 6.5 to 10.3 hr.No side-effects were observed.These results justify further exploration of the potential of heparin for high yield purified FVIII production.
Keywords: Heparin/factor VIII; Purified factor VIII; T½ factor VIII; Cryopreserved factor VIII; Small pool factor VIII